Exploring the role of NLRP3 inflammasome in diabetic nephropathy and the advancements in herbal therapeutics - Jin, Jiangyuan; Zhang, Mianzhi (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DN), a prevalent complication of diabetes mellitus (DM), is clinically marked by progressive proteinuria and a decline in glomerular filtration rate. The etiology and pathogenesis of DN encompass a spectrum of factors, including hemodynamic alterations, inflammation, and oxidative stress, yet remain incompletely understood. The NOD-like receptor pyrin domain-containing 3 (NLRP3) inflammasome, a critical component of the body's innate immunity, plays a pivotal role in the pathophysiology of DN by promoting the release of inflammatory cytokines, thus contributing to the progression of this chronic inflammatory condition. Recent studies highlight the involvement of the NLRP3 inflammasome in the renal pathology associated with DN. This article delves into the activation pathways of the NLRP3 inflammasome and its pathogenic implications in DN. Additionally, it reviews the therapeutic potential of traditional Chinese medicine (TCM) in modulating the NLRP3 inflammasome, aiming to provide comprehensive insights into the pathogenesis of DN and the current advancements in TCM interventions targeting NLRP3 inflammatory vesicles. Such insights are expected to lay the groundwork for further exploration into TCM-based treatments for DN.